Adoptive parenting and attachment: association of the internal working models between adoptive mothers and their late-adopted children during adolescence - Pace, Cecilia Serena; Di Folco, Simona; Guerriero, Viviana; Santona, Alessandra; Terrone, Grazia (Frontiers in Psychology, 2015)
Introduction. Recent literature has shown that the good outcome of adoption would mostly depend on the quality of adoptive parenting, which is strongly associated with the security of parental internal working models (IWMs) of attachment. Specifically, attachment states-of-mind of adoptive mothers classified as free and autonomous and without lack of resolution of loss or trauma could represent a good protective factor for adopted children previously maltreated and neglected. While most research on adoptive families has focused on pre-school and school-aged children, the aim of this study was to assess the concordance of IWMs of attachment in adoptive dyads during adolescence. Method. Our pilot-study involved 76 participants: 30 adoptive mothers (mean age=51.5±4.3), and their 46 late-adopted adolescents (mean age = 13.9 ± 1.6), who were all aged four to nine years old at time of adoption (M = 6.3 ± 1.5). Attachment representations of adopted adolescents were assessed by the Friend and Family Interview (FFI), while adoptive mothers’ state-of-mind with respect to attachment was classified by the Adult Attachment Interview (AAI). Adolescents’ verbal intelligence was controlled. Results. Late-adopted adolescents were classified as follows: 67% secure, 26% dismissing and 7% preoccupied in the FFI, while their adoptive mothers’ AAI classifications were 70% free-autonomous, 7% dismissing, and 23% unresolved. We found a significant concordance of 70% (32 dyads) between the secure-insecure FFI and AAI classifications. Specifically adoptive mothers with high coherence of transcript and low unresolved loss tend to have late-adopted children with high secure attachment, even if the adolescents’ verbal intelligence made a significant contribution to this prediction. Discussion. Our results provides an empirical contribution to the literature concerning the concordance of attachment in adoptive dyads, highlighting the beneficial impact of highly coherent states-of-mind of adoptiv